The Main Trends in the Development of Methods and Models for the Use of Digital Technologies in the Creation of Value Chains - N. M. Abdikeev; E. L. Moreva (Мир новой экономики)
In the modern world, value-added reproduction chains (VARC) are among the most important economic structures that have a mostly decisive impact on the production use and development of digital technologies (DT). This article analyses the features of their application, related problems and opportunities for their solution. The study showed that within the framework of different types of organisational and economic models of VARC, effective use of DT has its limits. They are driven by the specific nature of these models and require specific targeted actions to overcome and/or expand these limits. Mandatory participants in such processes include both the VARC and the state. The measures taken in this regard are integral complexes and should be carried out within the framework of the state policy of technological development in cooperation with the participants of the chains. Neglecting model features in the development and implementation of such actions is fraught with a reduction in the effectiveness of the efforts made and unjustified expenditure of resources. Taking into account the features of different models of DT use in the VARC is vital for the implementation of the economic policy of technological development of Russia. It makes it possible to increase the effectiveness of efforts to achieve the goals set by the President and the Government of the Russian Federation to ensure the transition of our country to the digital economy and accelerate this process. In this regard, the promising areas are the allocation of various organizational and economic models of the use of DT in the VARC of our country and/or in the international VARC with the participation of Russian entrepreneurs, as well as the formation in relation to them of particular sets of measures from different levels of government.